The role of natural organic ligands in dissolved copper (II) distribution at tropical coastal water - Mohamed, Khairul Nizam; Abdul Hamid, Nur Aina Atirah; Junairi, Aleef Syamim (Springer, 2023)
The vertical distribution of Cu(II) in dissolved and particulate phases was determined in the seawater at Pulau Redang, Terengganu, in April 2019. Our present results have shown a similar concentration of total dissolved Cu(II) at the upper layer (< 15 m depth) and bottom layer (> 15 m depth). At the upper layer, its concentration ranged between 10.05 and 20.81 nM, and at the bottom layer, it ranged between 4.37 and 24.03 nM. On the other hand, we found a low concentration of Cu(II) at the upper (0.05–0.88 nM) and bottom (0.05–0.51 nM) layers in the particulate phase. The distribution coefficient (KD) analysis has indicated that most of the Cu(II) existed in the dissolved phases throughout the water column during the study period. Our analysis on dissolved Cu(II) speciation has revealed the presence of weak ligand class ( L2), and its concentration (LT = 4.55–39.76 nM) has always been in excess of the dissolved Cu(II) concentration throughout the water column. The LT/dCu ratio (> 1.0) indicated that an existence of a saturated state condition and more than 99.0% of Cu(II) ion is organically complex to these natural organic ligands. This present study highlights that most of the Cu(II) exists in a dissolved organic complex at the tropical coastal waters. The presence of excess natural organic ligands as a chelator to the Cu(II) increases its solubility in the dissolved phase.